Elucidating the cleaning of complex food soil layers by in-situ measurements - Cuckston, G. L.; Suleiman, N.; Goodwin, J.; Groombridge, M.; Wilson, D. I. (Elsevier, 2022)
The mechanisms involved in cleaning a heterogeneous, multicomponent baked food soil off stainless steel surfaces in aqueous solutions were investigated using novel tools to quantify changes in the soil in situ and in real time: fluid dynamic gauging (thickness, voidage); millimanipulation (adhesive strength, removal force); TOC assays (soil leaching); and droplet image analysis (fat and oil release). Swelling of the soil was accompanied by a reduction in soil strength and preceded the release of oil droplets: the latter did not affect removal forces. The effect of pH, temperature, and surfactants (CTAB, SDBS and TX-100) was investigated and quantified using simple zeroth and first order kinetic models. Whilst increasing temperature from 20 °C to 50 °C enhanced swelling and reduced adhesion forces, the impact of pH and surfactant varied and simple rules to predict cleaning of this complex food soil could not be extracted.